Процесуальне право Ради Європи: принципи, система, динаміка - Анцупова, Тетяна Олександрівна; Анцупова, Татьяна Александровна; Antsupova, Tetyana О. (My University, 2014)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.11 - міжнародне право - Національний університет «Одеська юридична академія». - Одеса, 2014. Дисертація присвячена розробці концепції процесуального права Ради Європи. У роботі досліджено історію розвитку концепту та су часну доктрину міжнародного процесуального права, яка характеризується розумінням міжнародного процесу у широкому і вузькому сенсах. На основі широкого розуміння процесуального права, визначено, що процесуальне право Ради Європи - це правова цілісність, що ґрунтується на системі правових нормативів та цінностей і складається з упорядкованих процесуальних норм і принципів, які регулюють процесуальні правовідносини у рамках правотворчого і правореалізаційного процесів у Раді Європи. У роботі визначено співвідношення понять «правовий процес» і «правові процедури», систематизовано принципи і норми процесуального права Ради Європи. Виявлено функціональну структуру процесуального права Ради Європи. Виділено типи і види правового процесу у Раді Європи. Визначено та надано функціональну характеристику зовнішньої і внутрішньої правотворчості Ради Європи, а також установчого процесу, судового процесу, процесу моніторингу та процесу імплементації в Раді Європи.

Диссертация на соискание научной степени доктора юридических наук по специальности 12.00.11 - международное право - Национальный университет «Одесская юридическая академия». - Одесса, 2014. Диссертация посвящена разработке концепции процессуального права Совета Европы. В работе исследована история развития концепта и современная доктрина международного процессуального права, которая характеризуется пониманием международного процесса в широком и узком смыслах. На основе широкого понимания процессуального права, определено, что процессуальное право Совета Европы - это правовая целостность, основанная на системе правовых нормативов и ценностей и состоящая из упорядоченных процессуальных норм и принципов, регулирующих процессуальные правоотношения в рамках правотворческого и правореализационного процессов в Совете Европы. В работе определено соотношение понятий «правовой процесс» и «правовые процедуры», систематизированы принципы и нормы процессуального права Совета Европы. Выявлена функциональная структура процессуального права Совета Европы. Выделены типы и виды правового процесса в Совете Европы. Разработаны определения и представлена функциональная характеристика внешнего и внутреннего правотворчества Совета Европы, а также учредительного процесса, судебного процесса, процесса мониторинга и процесса имплементации в Совете Европы.

The thesis for Doctor of Law Degree by speciality 12.00.11 - International Law. - National University "Odessa Academy of Law". - Odessa, 2014. The thesis presents research which attempts to conceptually comprehend the Council of Europe procedural law based on a wide approach towards understanding the international procedural law. Herewith the author suggests the Council of Europe law to be considered as a special subsystem for the international- legal system. The determination of the place of the Council of Europe Law in the international legal system contributed to the study of the "European Law" concept. It was established that the correct use of the term "European Law" to refer to an independent legal system has not yet found a proper argument. It is proved that the «European law» in the narrow sense - is the system of legal norms, principles and values of the European Union and the Council of Europe, where common principles and values as a basis for its narrow sense. The thesis structure reflects the fulfillment of the general goal and major objectives. The author creates conceptual fundamentals of the Council of Europe procedural law (the conceptual and categorical apparatus, the system of principles and norms for the Council of Europe procedural law). The research relies on the studies in the field of general theory of law and the theory of international law while distinguishing between general and specific principles of the Council of Europe procedural law. The functional approach is used to systemize the norms of the Council of Europe procedural law. On the basis of philosophical, broad understanding of procedural law, it has been determined that the Council of Europe procedural law - is the legal integrity, based on a system of legal values and consisting of ordered procedural legal norms and principles governing legal proceedings under the law-making process and realization of Council of Europe law. It is proved that the understanding of the Council of Europe procedural law narrowly confined to the judicial process. The judicial process of the Council of Europe is a complex of legal procedures that govern the trial of the case before the European Court of Human Rights or the Administrative Tribunal of the Council of Europe. The judicial process of the Council of Europe is aimed at control the implementation by Member States of their obligations under the Convention for the Protection of Human Rights and Fundamental Freedoms or control the performance of official rules by the Council of Europe, respectively. The structure of the Council of Europe procedural law has been defined. The notion of "functional structure of the Council of Europe procedural law" is introduced following the functional approach. The main elements of this structure are distinguished and analyzed - the lawmaking and the realization of law. Derivative elements of the lawmaking include the external and internal lawmaking processes of the Council of Europe. Whereas the constitutive, judicial, monitoring processes, as well as the process of implementation of the Council of Europe law into the Member States' national legal systems are considered to be derivative elements of the realization of Council of Europe law. The theoretical and practical aspects of the Council of Europe law implementation in Ukraine have been analyzed. Implementation of international law (the Council of Europe law, in particular) is featured as a kind of realization of law process. The author analyzes the scientific and practical issues on the Council of Europe treaties implementation to the Ukrainian legal system, as well as legal support to the European Court of Human Rights' case law implementation and execution of judgments. The thesis equally presents the theoretical and practical issues on the Council of Europe procedural law.
Анцупова Т. О. Процесуальне право Ради Європи: принципи, система, динаміка : автореф. дис. ... докт. юрид. наук : 12.00.11 / Т. О. Анцупова; наук.консультант О. К. Вишняков; Нац. ун.-т "Одеська юридична академія". – Одеса, 2014. – 36 с.
Keywords: міжнародне процесуальне право; процесуальне право Ради Європи; правотворчість; установчий процес; судовий процес; процес моніторингу; процес імплементації; договори Ради Європи; Конвенція про захист прав людини і основоположних свобод; Європейський суд з прав людини; международное процессуальное право; процессуальное право Совета Европы; правотворчество; учредительный процесс; судебный процесс; процесс мониторинга; процесс имплементации; договоры Совета Европы; Конвенция о защите прав человека и основных свобод; Европейский суд по правам человека; the international procedural law; the Council of Europe procedural law; the law-making process; the constitutive process; judicial process; monitoring process; implementation process; Council of Europe treaties; the Convention for the Protection of Human Rights and Fundamental Freedoms; the European Court of Human Rights